Power of Partnership: Exploring Speech Acts in Movie Dialogues in Affecting Narrative and Character Development in "Bad Boys: Ride or Die" - Situmorang, Ryan Muhtadi Agha; Meisuri, Meisuri (English Teaching and Linguistics Journal (ETLiJ), 2025)
This study explores the use of speech act theory within the use of framework multimodal pragmatics to analyze the dialogues in Bad Boys: Ride or Die (2024). Focusing on the five main key of speech act categories such as assertives, directives, commissives, expressives, and declarations. The researchers investigate how these speech acts can make a character development, make an interesting narrative plot, and character relationships. Using a descriptive qualitative methodology, this research examines not only the verbal content of the dialogues but also the multimodal aspects such as body language, facial expressions, and tone, which work in order to reinforce and enhance the intended meanings. Through this approach, the study highlights the dynamic connection between verbal and non-verbal communication, revealing how speech acts influence the film’s emotional elements, such as loyalty, power, and emotional intensity. The findings demonstrate how speech acts drive plot advancement while also offering deeper insights into character motivations and emotional states. By using this multimodal framework, the research provides a comprehensive understanding of how pragmatic meaning is carried in cinematic dialogues, offering a valuable contribution to film studies and pragmatics. Ultimately, this study showcases the potential of combining multimodal pragmatics with speech act theory to enhance the analysis of modern action films and their intricate communication strategies.